A basic tool for the modeling of Marked-Controlled Reconfigurable Petri Nets - Llorens, Marisa; Oliver, Javier (Electronic Communications of the EASST, 2007)
In previous studies, we have introduced marked-controlled net rewriting systems and a subclass of these called marked-controlled reconfigurable Petri nets. In a marked-controlled net rewriting system, a system configuration is described as a Petri net, and a change in configuration is described as a graph rewriting rule. A marked-controlled reconfigurable Petri net is a marked-controlled net rewriting system where a change in configuration amounts to a modification in the flow relations of the places in the domain of the involved rule in accordance with this rule, independently of the context in which this rewriting applies. In both models, the enabling of a rule not only depends on the net topology, but also depends on the net marking according to control places. Even though the expressiveness of Petri nets and marked-controlled reconfigurable Petri nets is the same, with marked-controlled reconfigurable Petri nets, we can easily and directly model concurrent and distributed systems that change their structure dynamically. In this article, we present MCReNet, a tool for the modeling and verification of marked-controlled reconfigurable Petri nets.